PENGEMBANGAN RENCANA STRATEGIS DALAM PERENCANAAN KOTA YOGYAKARTA BERBASIS KARAKTER KHAS - , SEPTIONO EKO BAWONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta gained 26 achievements during 2008-2010, nationally. At the beginning 2014, New York Times declared that Yogyakarta is one world tourism destination. Yogyakarta is indicated as an Authentic City. Emphasizing strategic planning and creative city obtains the cityâs distinctiveness. The city vitals indicators that consist of four success dimensions figures out the Yogyakarta distinctiveness is the most value dimension than talent, innovative, and connected dimension. This research discusses the cityâs distinctiveness and its opportunity in developing decision making. Observing this dimension deeply, this research did field survey, interviewing key person and collecting secondary data. The data is used to update the previous research. Implementing factual analysis, SWOT analysis, aligned SWOT analysis and synthesis identifies the cityâs competitive advantages. It synthesizes huge possibilities of the cityâs action program. This research gives a description the Yogyakarta distinctiveness of Javanesse culture. It is the competitive advantages as the main aspect of city identity. They are: developing the most valued aspect that supporting the city image as an authentic city